Effects of Bisphosphonate Administration on Cleft Bone Graft in a Rat Model. (November 2017) - Cheng, Nicole; Park, Juyoung; Olson, Jeffrey; Kwon, Taewoo; Lee, Deborah; Lim, Rachel; Ha, Sandy; Kim, Reuben; Zhang, Xinli; Ting, Kang; Tetradis, Sotirios; Hong, Christine
Objective: Bone grafts in patients with cleft lip and palate can undergo a significant amount of resorption. The aim of this study was to investigate the effects of bisphosphonates (BPs) on the success of bone grafts in rats. Design: Thirty-five female 15-week-old Fischer F344 Inbred rats were divided into the following experimental groups, each receiving bone grafts to repair an intraoral CSD: (1) Graft/saline: systemic administration of saline and (2) systemic administration of zoledronic acid immediately following surgery (graft/BP/T0), (3) 1 week postoperatively (graft/BP/T1), and (4) 3 weeks postoperatively (graft/BP/T2). As an additional control, the defect was left empty without bone graft. Main Outcome Measures: Microcomputed tomography and histologic analyses were performed in addition to evaluation of osteoclasts through tartrate-resistant acid phosphatase staining. Results: Bone volume fraction (bone volume/tissue volume) for the delayed BP treatment groups (graft/BP/T1 = 45.4% ± 8.8%; graft/BP/T2 = 46.1% ± 12.4%) were significantly greater than that for the graft/saline group (31.0% ± 7.9%) and the graft/BP/T0 (27.6% ± 5.9%) 6 weeks postoperatively ( P < .05). Hematoxylin and eosin staining confirmed an evident increase in bone volume and fusion of defect margins with existing palatal bone in the graft/BP/T1 and graft/BP/T2 groups. The graft/BP/T0 group showed the lowest bone volume with signs of acute inflammation. Conclusions: Delayed BP administration following cleft bone graft surgery led to significant increase in bone volume and integration compared with saline controls. However, BP injection immediately after the surgery did not enhance bone volume, and rather, may negatively affect bone graft incorporation.